2022
DOI: 10.3390/foods11141997
|View full text |Cite
|
Sign up to set email alerts
|

The Application and Optimization of HIPEF Technology in the Processing of Juice from Strawberries Harvested at Two Stages of Ripeness

Abstract: The aim of this study was to investigate the influence of high intensity pulsed electric field (HIPEF) technology on the stability of total phenols, anthocyanins, hydroxycinnamic acids, flavonols, and condensed tannins in strawberry juices (Fragaria x ananassa Duch. cv. ‘Albion’) with different ripening stages (75% and 100%) and stored at +4 °C for 7 days. The HIPEF parameters studied were: (i) electric field strength (40 and 50 kV cm−1), (ii) frequency (100 and 200 Hz), and (iii) treatment duration (3 and 6 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 57 publications
2
3
0
Order By: Relevance
“…The levels of all studied bioactive compounds in the control samples, except for total phenolic compounds and FL, were significantly higher (p ≤ 0.01) in juices made from 100% ripe fruit than those of 75% ripeness, this is largely consistent with our previous findings [37]. As ripeness increased, TPC decreased in control samples, which is consistent with other literature [44].…”
Section: The Changes Of Bioactive Compounds In Strawberry Juices Unde...supporting
confidence: 92%
See 2 more Smart Citations
“…The levels of all studied bioactive compounds in the control samples, except for total phenolic compounds and FL, were significantly higher (p ≤ 0.01) in juices made from 100% ripe fruit than those of 75% ripeness, this is largely consistent with our previous findings [37]. As ripeness increased, TPC decreased in control samples, which is consistent with other literature [44].…”
Section: The Changes Of Bioactive Compounds In Strawberry Juices Unde...supporting
confidence: 92%
“…Storage positively influenced the contents of HCA and FL in control samples, while the contents of ANT decreased (Table 3). The value of HCA was 6.2% higher after 7 days of storage than after 0 days, which is in agreement with other literature reports [37,38]. The previous study confirmed that total and individual anthocyanins were degraded during storage according to first-order reaction kinetics, and the rate was strongly dependent on temperature [46].…”
Section: The Changes Of Bioactive Compounds In Strawberry Juices Unde...supporting
confidence: 92%
See 1 more Smart Citation
“…In order to better understand the synergetic relationships between the two technologies, the influence of both technologies on the quality of the juices tested was investigated. The process parameters were previously optimized for both HPU and PEF technologies [11], so the influence of treatment duration was investigated in this study.…”
Section: The Changes In Strawberry Juices After Hurdle Processing And...mentioning
confidence: 99%
“…Recently, pulsed electric field (PEF) and high-power ultrasound (HPU) technologies have shown promising results in the processing of fruit juices to obtain stable and biologically valuable functional products [10][11][12]. PEF technology is characterized by the inactivation of microorganisms and enzymes, which can be a substitute to thermal pasteurization [13].…”
Section: Introductionmentioning
confidence: 99%